If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-(x+4)=-6(x-6)
We move all terms to the left:
-(x+4)-(-6(x-6))=0
We get rid of parentheses
-x-(-6(x-6))-4=0
We calculate terms in parentheses: -(-6(x-6)), so:We add all the numbers together, and all the variables
-6(x-6)
We multiply parentheses
-6x+36
Back to the equation:
-(-6x+36)
-1x-(-6x+36)-4=0
We get rid of parentheses
-1x+6x-36-4=0
We add all the numbers together, and all the variables
5x-40=0
We move all terms containing x to the left, all other terms to the right
5x=40
x=40/5
x=8
| 29x+5x=44 | | x+2+4x-57=90 | | 4(z-57)+23=95 | | x/5-4=-10 | | f-2/3=32 | | 5.1=r-7.2 | | 51=9x-5-2x | | 2w-12=3w | | 10x-5=-5+10x | | -(-x+4)=2x+4-6 | | 18x-15+13x-11=180 | | 6x+2(x-5)*4x=44 | | 7k-3k=-16 | | 12x2-5x-25=0 | | 7(5x-2)=-329 | | 7x+10x=-46 | | 45+4.9t^2=33t | | -6.2=t+4.8 | | -4(-7x+5)=176 | | 8+28=4*w | | 4x-57=x+2 | | 8y+6-12=2y+9-3y | | 2(9y-1)=99-7(3-4y | | 5+2x5=x | | x+2=4x-57 | | 10-4x=3x+10 | | 7x-7-6x-16=1+4x | | -4(-6x-3)=156 | | 10m+50=70 | | 18+18=z*6 | | 3x+6=6x-4.5 | | 1/3(m+210+2/3m=-2 |